Pentingnya Pemahaman Literasi Pasar Modal, Harga Saham Dalam Memilih Keputusan Berinvestasi Pada Era Digital - Putri, Silviana Aulia; Pratama, Ine Hannisa (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
In today's digital era, investors can easily get information regarding how to invest. But not all technology users understand how to choose the right investment decisions. The aim of this research is to provide an understanding of capital market literacy and stock prices in choosing investment decisions in the digital era so that you know about the objectives, risks and rate of return on investment. The writing method used by the author is a literature review sourced from journal references from 2018-2023 related to the theme of understanding capital market literature, stock prices and investment decisions. Based on the results of the literature review carried out, understanding capital market literacy and stock prices is very important in choosing investment decisions. This is proven by the results of this research, namely, by providing an understanding of capital market literacy and stock prices, investors in the digital era will be greatly helped in making decisions to avoid losses and gain profits with low risk. On the other hand, investors who are not influenced by the variables of understanding capital market literacy and stock prices have a tendency not to consider the risks that will be faced in the future in the shares they invest in.